Searching for the missing soldier: identifying casualties from the First World War - Márquez-Grant, Nicholas; Wessling, Roland; Öfele, Angela; Moore, Victoria (University of Valencia, 2019)
In recent years there has been an increase in the numbers of archaeologists and physical anthropologists involved in searching, locating and assisting in the identification of war casualties. These scientists have played an invaluable role within a larger team of professionals, working together to provide a dignified burial to those who fell for their country and remembering them. This paper reviews some of the work undertaken in Europe with regard to WWI casualties and how the war missing are located and ultimately identified when possible, bringing also some closure to their living relatives.
Keywords: World War I; human remains; forensic anthropology; archaeology; DNA